PEMBERIAN EDUKASI PRAKTEK INISIASI MENYUSUI DINI (IMD) TERHADAP KEBERLANGSUNGAN PEMBERIAN ASI EKSKLUSIF PADA IBU BARU MELAHIRKAN DI RUANG OBSTETRI RSUP DR. KARIADI SEMARANG - Nikmatunazilah, Nikmatunazilah; Wulaningsih, Indah (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Background: Efforts that can be made to support the success of exclusive breastfeeding include early initiation of breastfeeding. Factors that can influence the implementation of Early Breastfeeding Initiation are the level of knowledge of the baby's mother, lack of family attitudes and support in implementing, and health workers who do not communicate the importance of early breastfeeding initiation. Purpose: to determine the benefits of providing education on the practice of Early Breastfeeding Initiation on the continuation of exclusive breastfeeding for new mothers in the Obstetrics Room at RSUP. Dr. Kariadi Semarang. Method: This type of research uses descriptive case studies. The subjects of this writing are patients who experienced postpartum casarea, with a focus on the study of providing education on early initiation of breastfeeding on the continuation of exclusive breastfeeding. Instruments used were leaflets regarding early initiation of breastfeeding and exclusive breastfeeding. Results: Two respondents were primiparous mothers and had no experience in breastfeeding. Evaluation obtained was that both respondents understood and comprehended the information provided. Conclusion: It is proven that there is an increase in knowledge regarding the practice of early initiation of breastfeeding after being given education using leaflets regarding early initiation of breastfeeding and exclusive breastfeeding